Examining the relation of cerebral lateralization, hand preference and grip strength in elite fencing athletes - Gümüs, M.; Akalin, T. C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Cerebral Lateralization is defined as the anatomical and functional differentiation between the right and left hemispheres of the brain. Each hemisphere has different functions and the dominant hemisphere fulfils its duties better than the other. One of the hemispheres being heavier than the other is an anatomical lateralization; however, the hand preference, which shows the functional asymmetry related to the brain best, is accepted as a functional cerebral lateralization. The grip strength in hand functions is a significant function for the continuity of daily life activities. Therefore, the grip strength is accepted as an objective measurement in performance evaluation of the upper extremity. Accordingly, the goal of this study is to examine the relation of cerebral lateralization, hand preference and grip strength in fencing, which provides health, endurance, speed, strength, agility, flexibility, balance, reflexes, coordination, intuition, timing ability, quick thinking and decision-making for your body. Methods: 117 elite fencing athletes, attended Interuniversity Fencing Championship, voluntarily participated in the study whose ages range from 18 to 25. Hand preference was confirmed by Oldfield Survey and evaluated between +100 and -100 according to the Geschwind Score. Two sportsmen were excluded from the study as they were ambidextrous. In the intergrouping comparisons right-handed and dominant right-handed were grouped as right-handed, left-handed and dominant left handed were grouped as left-handed. Hand grip strength was measured by Jamar hydraulic dynamometer. Data was evaluated after it was transferred to the SPSS for Windows 21.0 programme. Average values were shown as "arithmetic average * standard deviation". In the intergrouping comparisons Mann-Whitney U and Pearson correlation analysis were used. Analysis results were evaluated in the %95 confidence interval. Correlation factor was adopted as 0.000-0.250 weak or none, 0.251-0.500 intermediate, 0.501-0.750 strong, 0.751-1.000 very strong relationship. Results: %48,1 of the subjects attended our study were dominant right-handed, %40,3 were right-handed, %10,2 were left-handed and %1,4 were dominant left-handed. Dominant hand grip strength was 44.2 for the right-handed and 43.9 for the left-handed. For the nondominant hand it was in order of 42.8 and 41.5. Discussion: This functional laterality may due to the dominance of left hemisphere. The results were compared to those in literature. It is significant to make similar evaluations intended for hand and hand performance on more subjects and different ages and different competition categories in which hand performance is improved by active use.